Non-erosive reflux disease compared with erosive esophagitis with regards to acid reflux and symptom patterns - Mojgan FROOTAN; Sahar CHOOBTASHANI; Eznollah AZARGASHB; Pourhoseingholi Mohamad AMIN; Moosapour HAMIDE; Mohamad Reza ZALI; Ashraf HALEH (Turkish Journal of Gastroenterology, 2019)
-